Evaluating a wayfinding video. (13th July 2018) - Shaw, Nicole; Hitch, Danielle; Lyons, Nikki; Alharthi, Khalid; Grant, Briony; Laupert, Ben
Summary: Background: Many occupational therapy students experience anxiety and distraction when entering a new setting at the beginning of a clinical placement. Orientation processes may provide students with the information they need to feel more comfortable in an unfamiliar clinical setting. The aim of this project was to evaluate a revised wayfinding video for first‐ and second‐year occupational therapy students, with a particular focus on reducing anxiety. Methods: A revised version of a wayfinding video (with a duration of 3 minutes and 40 seconds) was created by final‐year occupational therapy students and then evaluated using a paper‐based descriptive survey. All data were analysed using a content analysis approach. Results: A total of 71 responses were received, demonstrating a response rate of 47%. The students indicated that the video addressed the main sources of pre‐placement anxiety and supported their pre‐existing anxiety management strategies. Anxiety‐reducing features of the video included an overview and visual introduction to the facility, hearing the positive experiences of other students, the provision of placement expectations and an introduction to the student coordinators. All but two of the students indicated that they would watch the video if it were attached to their welcome pack. Many occupational therapy students experience anxiety and distraction when entering a new setting Conclusions: The revised wayfinding video addressed many of the students' anxieties about commencing placement and now forms part of a broader suite of student orientation materials. There are several limitations to the development of wayfinding videos, but they are surmountable via collaboration and investment in careful planning.